Lymphadenopathies: A Retrospective Study of Epidemiology, Characteristics, Diagnosis and Treatment Outcomes of Patients in a Tertiary Hospital in Mogadishu-Somalia - Kıratlı K; Bulut M; Ali MA; Aysin M; Ali AM; Mohamed Hirsi I; Bashir AM (Infection and Drug Resistance)
Kazım Kıratlı,1 Muhammet Bulut,2 Mukhtar Abdullahi Ali,1 Murat Aysin,3 Ahmed Mohamed Ali,1 Ibrahim Mohamed Hirsi,4 Ahmed Muhammad Bashir5 1Mogadishu Somalia Turkey Recep Tayyip Erdoğan Training and Research Hospital, Department of Infectious Diseases and Clinical Microbiology, Mogadishu, Somalia; 2Sancaktepe Şehit Prof. Dr. Ilhan Varank Training and Research Hospital, Department of Radiology, Istanbul, Turkey; 3Balikesir University Faculty of Medicine, Department of Public Health, Balikesir, Turkey; 4Mogadishu Somalia Turkey Recep Tayyip Erdoğan Training and Research Hospital, Department of Pediatrics, Mogadishu, Somalia; 5Mogadishu Somalia Turkey Recep Tayyip Erdoğan Training and Research Hospital, Department of Internal Medicine, Mogadishu, SomaliaCorrespondence: Kazım Kıratlı, Mogadishu Somalia Turkey Recep Tayyip Erdoğan Training and Research Hospital, Department of Infectious Diseases and Clinical Microbiology, Mogadishu, Somalia, Email drkazimkiratli@gmail.comIntroduction: Lymphadenopathies, which can be caused by infections, malignant diseases, autoimmune disorders, and many other diseases, pose a challenge to clinicians in sub-Saharan Africa, as well as all over the world. The purpose of this research was to identify the clinical and diagnostic characteristics of Somalian patients suffering from swollen lymph nodes.Methods: Under the purview of this study, the diagnoses, patient clinical courses, and treatment outcomes were ascertained retrospectively by analyzing the biochemical, microbiological, radiological, and pathological data of the cases in all age groups who underwent therapy for lymphadenitis at Mogadishu Somali Turkey Recep Tayyip Erdoğan Training and Research Hospital between January 2016 and September 2023.Results: During the study period, 317 patients were followed up, with 53.3% of the patients as female, 46.7% as male, 28.1% as pediatric, 63.1% as adult, and 8.8% were elderly patients. With 58.7% of diagnoses, tuberculous lymphadenitis was the most common, pursued by malignant causes (21.8%). The most commonly affected lymph node was the cervical region, the symptom detected was lymph node swelling, the radiological method used was ultrasonography, and the biopsy method was fine needle aspiration biopsy. It was determined that benign conditions, including tuberculosis were more common in pediatric group and younger adults (p< 0.001), and weight loss was a significant in terms of malignancy and tuberculosis (p< 0.001). White blood cell value (p< 0.001), erythrocyte sedimentation rate (p< 0.001), and C-reactive protein (p:0.001) revealed differences across the diagnostic groups.Conclusion: Almost two-thirds of patients were diagnosed with tuberculosis lymphadenitis. Our finding revealed tuberculosis as the commonest cause of lymphadenopathy followed by malignant causes. Therefore, before screening for malignant causes, tuberculosis should be the first diagnosis considered in Somalia, particularly in a patient presenting with weight loss and swelling of the lymph nodes.Keywords: immunization, lymphadenopathy, Somalia, sub-Saharan Africa, tuberculosis